ECONOMIC RESILIENCE OF AGRIBUSINESS HOUSEHOLDS IN PUTIH RIVER REGION FOLLOWING THE 2010 MERAPI VOLCANISM EVENTS - , Bujed Pamungkas, Dr. Rini Rachmawati, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Motivated by preliminary field visit findings about the presence of ability to minimise loss resulting from impacts of the 2010 Merapi volcanism events on economic activity performed by agribusiness households in Putih River region, this research aimed at constructing economic resilience theory to explain the process in which this ability developed, measuring economic resilience of agribusiness households in Putih River region, as well as developing economic resilience model.